2004
DOI: 10.1152/ajpendo.00487.2003
|View full text |Cite
|
Sign up to set email alerts
|

Possible involvement of the α1 isoform of 5′AMP-activated protein kinase in oxidative stress-stimulated glucose transport in skeletal muscle

Abstract: Possible involvement of the ␣1 isoform of 5ЈAMP-activated protein kinase in oxidative stressstimulated glucose transport in skeletal muscle. Am J Physiol Endocrinol Metab 287: E166 -E173, 2004. First published March 16, 2004 10.1152/ajpendo.00487.2003.-Recent studies have suggested that 5ЈAMP-activated protein kinase (AMPK) is activated in response to metabolic stresses, such as contraction, hypoxia, and the inhibition of oxidative phosphorylation, which leads to insulin-independent glucose transport in skele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
184
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(189 citation statements)
references
References 59 publications
5
184
0
Order By: Relevance
“…Furthermore, Comp C treatment abolished AICAR-induced JNK as well as caspase-3 activation, demonstrating that AICAR is acting in the sequence AMPK-JNK-caspase-3. AMPK activation through ROS has been previously demonstrated among others in endothelial cells (36), HepG2 hepatocarcinoma cells (37) and vascular smooth muscle cells (38) which may occur before or without alteration in the ATP/AMP ratio (38)(39)(40). In this respect it has been recently shown that physiologically relevant concentrations of H 2 O 2 can activate AMPK through oxidative modification of the AMPKα subunit, and it was discussed that AMPK activation, in addition to being a response to alterations in intracellular metabolic pathways, is directly influenced by cellular redox status (41).…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, Comp C treatment abolished AICAR-induced JNK as well as caspase-3 activation, demonstrating that AICAR is acting in the sequence AMPK-JNK-caspase-3. AMPK activation through ROS has been previously demonstrated among others in endothelial cells (36), HepG2 hepatocarcinoma cells (37) and vascular smooth muscle cells (38) which may occur before or without alteration in the ATP/AMP ratio (38)(39)(40). In this respect it has been recently shown that physiologically relevant concentrations of H 2 O 2 can activate AMPK through oxidative modification of the AMPKα subunit, and it was discussed that AMPK activation, in addition to being a response to alterations in intracellular metabolic pathways, is directly influenced by cellular redox status (41).…”
Section: Discussionmentioning
confidence: 94%
“…AMPK activity was determined as described previously, with slight modifications (40). Frozen muscles were homogenized in ice-cold lysis buffer (1:60, wt/vol) containing 20 mM HEPES (pH 7.4), 1% Triton X-100, 50 mM sodium chloride, 50 mM sodium fluoride, 5 mM sodium pyrophosphate, 2 mM dithiothreitol, 4 mg/l leupeptin, 50 mg/l trypsin inhibitor, 0.1 mM benzamidine, and 0.5 mM phenylmethylsulfonyl fluoride and then centrifuged at 14,000 g for 20 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Frozen muscles were homogenized in ice-cold lysis buffer (1:60, wt/vol) containing 20 mM HEPES (pH 7.4), 1% Triton X-100, 50 mM sodium chloride, 50 mM sodium fluoride, 5 mM sodium pyrophosphate, 2 mM dithiothreitol, 4 mg/l leupeptin, 50 mg/l trypsin inhibitor, 0.1 mM benzamidine, and 0.5 mM phenylmethylsulfonyl fluoride and then centrifuged at 14,000 g for 20 min at 4°C. The supernatants (200 g of protein) were immunoprecipitated with isoform-specific antibodies directed against the ␣1-or ␣2-subunit of AMPK (40) and protein A-Sepharose beads. The immune complex was washed extensively with 240 mM HEPES (pH 7.0) and 480 mM sodium chloride.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations